2019
DOI: 10.1186/s13287-019-1255-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining the fundamental biology of a novel population of directly reprogrammed human neural precursor cells

Abstract: Background Cell reprogramming is a promising avenue for cell-based therapies as it allows for the generation of multipotent, unipotent, or mature somatic cells without going through a pluripotent state. While the use of autologous cells is considered ideal, key challenges for their clinical translation include the ability to reproducibly generate sufficient quantities of cells within a therapeutically relevant time window. Methods We performed transfection of three dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 58 publications
0
17
0
1
Order By: Relevance
“…Directly reprogrammed neural precursor cells (drNPC) were kindly provided by New World Laboratories, Inc. (Laval, Quebec, Canada). They were prepared from cultured adult bone marrow MSC by direct reprogramming, skipping the pluripotency stage in the programming of human bone marrow MSC using transient transfection with the following 3 factors: Musashi−1 (Msi1), Neurogenin−2 (Ngn2), and methyl−CpG binding domain protein 2 (MBD2) ( Ahlfors et al, 2019 ). Cells were cultured in Petri dishes (SPL Life Sciences, South Korea) coated with human laminin (L2020, Sigma-Aldrich), at 37°C in the atmosphere of 5% CO 2 and 5% O 2 in complete NeuroCult TM -XF Proliferation medium (StemCell Technologies) supplemented with B27 (1×, Gibco), 20 ng/ml of epidermal growth factor (EGF, Biolegend), 40 ng/ml of fibroblast growth factor-2 (FGF-2, Biolegend) and 100 ng/ml heparin (Stem cells technology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Directly reprogrammed neural precursor cells (drNPC) were kindly provided by New World Laboratories, Inc. (Laval, Quebec, Canada). They were prepared from cultured adult bone marrow MSC by direct reprogramming, skipping the pluripotency stage in the programming of human bone marrow MSC using transient transfection with the following 3 factors: Musashi−1 (Msi1), Neurogenin−2 (Ngn2), and methyl−CpG binding domain protein 2 (MBD2) ( Ahlfors et al, 2019 ). Cells were cultured in Petri dishes (SPL Life Sciences, South Korea) coated with human laminin (L2020, Sigma-Aldrich), at 37°C in the atmosphere of 5% CO 2 and 5% O 2 in complete NeuroCult TM -XF Proliferation medium (StemCell Technologies) supplemented with B27 (1×, Gibco), 20 ng/ml of epidermal growth factor (EGF, Biolegend), 40 ng/ml of fibroblast growth factor-2 (FGF-2, Biolegend) and 100 ng/ml heparin (Stem cells technology).…”
Section: Methodsmentioning
confidence: 99%
“…Direct reprogramming is likely to deliver less risky cell products. In this study we used directly reprogrammed NPC (drNPC) derived from human bone marrow mesenchymal cells ( Ahlfors et al, 2019 ). These cells or their oligodendrogenic derivatives proved to be therapeutically effective in rodent ( Nagoshi et al, 2008 ; Nori et al, 2018 ) and non-human primate ( Baklaushev et al, 2019 ) models of spinal cord injury and in a mouse focal ischemic stroke model with formation of small cortical infarctions ( Vonderwalde et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we examine the galvanotactic response of clinically relevant human directly reprogrammed NPCs (drNPCs). 9 In a 2D in vitro model, we show that drNPCs undergo rapid and directed migration in the presence of a 250 mV/mm EF, and that the direction of migration (anodal vs. cathodal) can be modulated by the substrate stiffness. We have found that the migration of drNPCs under an applied EF is independent of secreted factors from neighboring cells and extracellular pH.…”
Section: Introductionmentioning
confidence: 76%
“…drNPCs were generated from mature human bone marrow cells as previously described. 9 The drNPCs were cultured in low oxygen conditions in basal medium (NeuroCultÔ NS-A Basal Medium Human -Catalog #05750) containing 10% proliferation supplement (NeuroCult Proliferation Supplement Human -Catalog #05753), fibroblast growth factor-2 (FGF-2; 30 ng/mL, Peprotech), epidermal growth factor (EGF, 20ng/mL; Peprotech), and heparin (100 lg/mL; Scientific Protein Laboratories), termed EFH. drNPCs were cultured as free-floating colonies (neurospheres) for 3-7 days on an ultra-low attachment 24-well plate (CLS3473 Sigma-Aldrich).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation